2019
DOI: 10.1111/1462-2920.14614
|View full text |Cite
|
Sign up to set email alerts
|

Feeding modes shape the acquisition and structure of the initial gut microbiota in newborn lambs

Abstract: SummaryEarly gut microbial colonization is important for postnatal metabolic and immune development. However, little is known about the effects of different feeding modes (suckling versus bottle‐feeding) or microbial sources on this process in farm animals. We found that suckled and bottle‐fed newborn lambs had their own distinct gut microbiota. Results from 16S rRNA gene sequencing and qPCR showed that, compared with suckling, bottle feeding significantly increased the abundances of Escherichia/Shigella, Buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 80 publications
4
36
1
Order By: Relevance
“…Like the findings in feces of humans ( Zhang et al, 2009 ; Fallani et al, 2011 ; Koenig et al, 2011 ; Faith et al, 2013 ) and animals [e.g., cattle ( Durso et al, 2010 ; Alipour et al, 2018 ), sheep ( Bi et al, 2019 ), pigs ( Looft et al, 2014 ), and monkeys ( Yasuda et al, 2015 )], the phyla Firmicutes, Bacteroidetes, and Proteobacteria were predominant in the fecal and rumen microbiota of goat kids and their mothers. The highest abundance of Proteobacteria and high variability in alpha diversity were present in the fecal microbiota of goat newborns on day 0, which is also true in hindguts of other goat breeds ( Jiao et al, 2016 ; Li et al, 2019 ) and the rumen of calves ( Rey et al, 2014 ).…”
Section: Discussionmentioning
confidence: 53%
“…Like the findings in feces of humans ( Zhang et al, 2009 ; Fallani et al, 2011 ; Koenig et al, 2011 ; Faith et al, 2013 ) and animals [e.g., cattle ( Durso et al, 2010 ; Alipour et al, 2018 ), sheep ( Bi et al, 2019 ), pigs ( Looft et al, 2014 ), and monkeys ( Yasuda et al, 2015 )], the phyla Firmicutes, Bacteroidetes, and Proteobacteria were predominant in the fecal and rumen microbiota of goat kids and their mothers. The highest abundance of Proteobacteria and high variability in alpha diversity were present in the fecal microbiota of goat newborns on day 0, which is also true in hindguts of other goat breeds ( Jiao et al, 2016 ; Li et al, 2019 ) and the rumen of calves ( Rey et al, 2014 ).…”
Section: Discussionmentioning
confidence: 53%
“…The combinative administration of FOS and garlic might have an impact on ruminant health, as they have shown to limit the ability of potential pathogen growth and the incidence of diarrheal diseases. This could be particularly relevant in lamb farms where lambs are not fed with breast milk, as the ones from this study, considering the recent results obtained by Bi et al [21] were they correlated bottle-feeding with an increased abundance of potential pathogens such as Escherichia/Shigella and diarrheal incidences. Escherichia is a well-known member of the normal intestinal microbiota of animals, and it comprises a very versatile genus including harmless commensal and pathogenic strains that can provoke intestinal diseases, such as diarrhea, which is the main cause of morbidity and mortality in newborn ruminants [21,61].…”
Section: Discussionmentioning
confidence: 72%
“…This could be particularly relevant in lamb farms where lambs are not fed with breast milk, as the ones from this study, considering the recent results obtained by Bi et al [21] were they correlated bottle-feeding with an increased abundance of potential pathogens such as Escherichia/Shigella and diarrheal incidences. Escherichia is a well-known member of the normal intestinal microbiota of animals, and it comprises a very versatile genus including harmless commensal and pathogenic strains that can provoke intestinal diseases, such as diarrhea, which is the main cause of morbidity and mortality in newborn ruminants [21,61]. Some studies have reported the effect of FOS, Bifidobacterium and Lactobacillus in hindering the attachment of Escherichia, to the epithelial cell surfaces and thus reducing the incidence of diarrheal processes [29,67,68].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations